Study on gravel soil strength degradation and its influence on the slope stability in reservoir bank fluctuating zone. (April 2022) - Wang, Wenda; Wang, Pengcheng; Zhang, Zhenhua
Highlights: The permeability test was carried out under the condition of considering particle loss. The variation law of particle loss with periodic infiltration times was obtained. Through the test, the variation law and fitting curve of shear strength of gravelly soil with infiltration times were obtained. The necessity of considering soil strength deterioration in calculating the stability of gravel soil bank slope was proved. Abstract: During the operation of the reservoir, due to the periodic fluctuation of the reservoir water level, a certain depth of fluctuation zone of the reservoir bank slope will be formed. The fine particles in the soil of the fluctuation zone will erode and migrate with the seepage of the reservoir water, resulting in the deterioration of soil strength parameters in different degrees, and even affecting the stability of the bank slope in severe cases. Because of the continuous particle size distribution and large porosity of gravel soil bank slope, under the periodic seepage of reservoir water, it is more likely to have serious particle loss, and the accumulated soil strength degradation caused by particle loss will further cause bank deformation, even instability. This paper carries out periodic pressure permeability tests on gravel soil samples to obtain the change law of particle loss rate and the degradation law of strength characteristics, and researches its influence on the slope stability. The research results show that the periodic seepage will degrade the strength of gravelly soil. With the increase of infiltration times, the deterioration range gradually decreases and the strength tends to be stable.